Gender integration strategy: approaches for research and development in a refugee context and other settings in Africa - Mendum, Ruth M.; Gebrezgabher, Solomie A.; Njenga, Mary (International Water Management Institute, 2022)
"The purpose of this brief is twofold: to frame the purpose of gender integration for use in displaced and disenfranchised communities in Africa; and to specify how a theory of gender integration and transformation can be applied to specific program objectives, including the design and development of projects; design and use of data collection protocols; development and delivery of training materials; and communication and outreach."